CORRELATION BETWEEN HORMONAL STATUS OF ESTROGEN RECEPTOR AND MALIGNANCY DEGREE OF INVASIVE DUCTAL BREAST CANCER - Trisna, Windy Ayustyas; Sahudi, Sahudi; Kusumastuti, Etty Hary (Majalah Biomorfologi, 2021)
Background: Globocan data in 2018 shows the cancer incidence in Indonesia. The highest case in women is breast cancer. The chance of survival for patients with high malignancy (Grade III) is only 11.86%, while for patients with low malignancy (Grade I) can reach 71.69%. Estrogen exposure is a risk factor for breast cancer. The hormone causes its effect through the estrogen receptor which is a core protein. Patients with positive receptor have 5 and 10 years survival rate which is better than patients with negative estrogen receptor. Objective: To identify correlation between hormonal status of estrogen receptor and malignancy degree of invasive ductal breast cancer. Materials and Methods: This research was an observational analytic study. The sample used was patients' medical record data in 2015-2017 in Anatomic Pathology Unit, Central Laboratory Installation, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Results: The data used were 694 patients medical record in 2015-2017. Approximately 56 patients (86%) had hormonal status of positive estrogen receptor with grade I cancer, 180 patients (70%) were in grade II, and 217 patients (45%) were in grade III. Approximately 9 patients (14%) had hormonal status of negative estrogen receptor with grade I cancer, 71 patients (28%) were in grade II, and 161 patients (34%) were in grade III. The result using Chi-Square test found Chi-Square value of 27.413 with a significance of 0.000 (p <0.01). Conclusion: There was a positive correlation between the hormonal status of estrogen receptor and malignancy degree of invasive ductal breast cancer.